Free-form ceramic vault system: taking ceramic additive manufacturing to real scale - Carvalho, João António Nogueira (2019)
The use of Additive Manufacturing (AM) for the production of architectural components has more and more examples attesting the possibilities and the advantages of its application. At the same time we seen a fast grow of the usage of ceramic materials to produce fully customised architectural components using Layer Deposition Modelling (LDM) techniques. However, the use of this material, as paste, leads to a series of constraints relative to its behaviour when in the viscous state, but also in the drying and firing stages. Thus, when ceramic dries, the retraction effects may be a barrier to the regular use of this material to build future architectural systems. In this sense, it is important to study the material behaviour and know how to control and use it as a primary construction material. To do that we present the challenges and outcomes of project Hexashade, a ceramic vault shading system prototype whose geometry and internal structure is defined according to the solar incidence. This paper explain how we expect to build a real scale self-supporting prototype.